Ethnic identity, collective self-esteem and academic self-efficacy among Black and White tertiary students - Thomas, Angela Tsholofelo; Wagner, Claire (South African Journal of Higher Education, 2016)
The current study investigated the relationship between ethnic identity, collective self-esteem and academic self-efficacy among a sample of Black (n = 81) and White (n = 55) students at a higher learning institution (HLI). For the Black sample, positive correlations were found between ethnic identity and academic self-efficacy, as well as between collective self-esteem and academic self-efficacy. For the White sample, however, no correlation was found between any of these variables. These findings are discussed in relation to the Black respondents’ possible experiences and perceptions of racial discrimination in the context of the study, wherein they are a minority. This is also taking into account the history of institutionalised discrimination against Blacks during the apartheid era and the fact that the study takes place in a historically White HLI.